Spermatogonial stem cells protein identification in in vitro culture from non-obstructive azoospermia patient - Abdul Wahab, Azantee Yazmie (Universiti Sains Malaysia, 2016)
BACKGROUND: Spermatogonial stem cells (SSCs) are classifiedas a unique adult stem cells that have capability to propagate, differentiate, and transmit genetic information to the next generation. Studies on human SSCs may help resolve male infertility problems, especially in azoospermia patients. Therefore, this study aims to propagate SSCs in-vitro with a presence of growth factor and detect SSC-specific protein cell surface markers. METHODS: The sample was derived from non-obstructive azoospermic (NOA) patient. The disassociation of SSCs was done using trypsin. Specific cultures in serum-free media with added basic fibroblast growth factor (bFGF) were developed to support self-renewal division. This undifferentiated protocol was performed for 49 days. Cells were analysed on days 1, 7, 14, 21, and 49. RESULTS: Human SSCs began to aggregate and form colonies after 14 to 21 days in specific culture. Then, the cells were successful expanded and remained stable for a duration of 49 days. Four specifics markers were identified using immunofluorescence in SSCs on day 49: ITGα6, ITGβ CD9, and GFRα1. CONCLUSION: This approach of using in vitro culture with additional growth factor is able to propagate SSCs from non-obstructive azoospermia patient via detection of protein cell surface markers.